Gamification to Identify Software Development Team Members' Profiles (2018)
Nowadays, the software development means teamwork, in both industry and academia. Because of the soft skills and knowledge that each team member brings to the team, for high performance teams, the human factor turns out to be a key element. Therefore, building a well-structured team implies to consider its members' individualities, which will compose the coexistence that will directly impact the team. In order to observe collaboration in a similar to real life situation, in this paper we propose the use of a contraption based on the Rube Goldberg machine to gamify the identification of software development team roles focusing on knowledge, skills and interactive styles toward the integration of high performance teams. A virtual reality tool was developed to provide an attractive way to support the integration of high performance teams for software engineering. This paper includes both the description of the virtual environment and the first results of implementing it. The first results show that after using the virtual environment the teams obtained better performance. © 2018, Springer Nature Switzerland AG.